1995
DOI: 10.1063/1.468990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of the thermal decomposition of 2,3-diazabicyclo(2.2.1)hept-2-ene

Abstract: Microwave spectrum, dipole moment, and the conformation of 7oxabicyclo[4.1.0]hept3ene J. Chem. Phys. 68, 4027 (1978); 10.1063/1.436300 Lowfrequency vibrational spectra and conformations of bicyclo [3.2.0] hept6ene and 2oxabicyclo [3.2.0] hept6eneThe reaction dynamics of the thermal gas-phase decomposition of 2,3-diazabicyclo ͑2.2.1͒hept-2-ene-exo, exo-5,6-d 2 have been investigated using classical trajectory methods on a semiempirical potential-energy surface. The global potential is written as a superposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…First, experiments showed that N 2 loss results in bicyclo products 3 and 4 with a nonstatistical preference for the exo product in a 4.7:1 ± 0.9 (exo:endo) ratio. , The statistical ratio would be 1:1 if the intervening 1,3-singlet diradical intermediate 2 were to undergo complete IVR prior to C–C bond formation. Second, several qualitative theories for the origin of selectivity have been proposed, beginning with Roth and Martin, , Allred and Smith, and culminating with Carpenter’s in-depth description that the nonstatistical exo:endo ratio results from a relatively low barrier (∼2 kcal/mol) for transition-state TS2 ( endo-TS2 and exo-TS2 , see Scheme ), which results in C–C bond formation without IVR. , More specifically, Carpenter’s description focused on the out-of-plane bending motion of the methylene (CH 2 ) bridge group that leads to the unexpected excess of exo product 3 , and this rationale was qualitatively supported by classical trajectory analyses and experiments in supercritical propane . Third, density functional theory (DFT) quasiclassical trajectories have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…First, experiments showed that N 2 loss results in bicyclo products 3 and 4 with a nonstatistical preference for the exo product in a 4.7:1 ± 0.9 (exo:endo) ratio. , The statistical ratio would be 1:1 if the intervening 1,3-singlet diradical intermediate 2 were to undergo complete IVR prior to C–C bond formation. Second, several qualitative theories for the origin of selectivity have been proposed, beginning with Roth and Martin, , Allred and Smith, and culminating with Carpenter’s in-depth description that the nonstatistical exo:endo ratio results from a relatively low barrier (∼2 kcal/mol) for transition-state TS2 ( endo-TS2 and exo-TS2 , see Scheme ), which results in C–C bond formation without IVR. , More specifically, Carpenter’s description focused on the out-of-plane bending motion of the methylene (CH 2 ) bridge group that leads to the unexpected excess of exo product 3 , and this rationale was qualitatively supported by classical trajectory analyses and experiments in supercritical propane . Third, density functional theory (DFT) quasiclassical trajectories have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Insight in the dynamical aspects of the thermal decomposition of ANTA could be obtained by using molecular dynamics calculations if an accurate potential energy surface (PES) that describes the main geometric, spectroscopic, and thermochemical parameters of the reactant, products, and transition states were formulated. We have previously developed and used such PESs in molecular dynamics and Monte Carlo simulations of a number of cyclic nitro and diaza compounds, such as hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) , and 2,3-diazabicyclo[2.2.1]hept-2-ene. , In the present paper, we undertake the first step in the development of a reliable PES for ANTA by constructing a force field for the 2 H -ANTA molecule in the gas phase. This force field is based on the geometries and the scaled fundamental frequencies determined predicted by ab initio calculations at the MP2/6-311+G(d,p) level.…”
Section: Introductionmentioning
confidence: 99%
“…The photodenitrogenation displays a viscosity effect, which demonstrates that a product bifurcation operates, with the 1 DZ diradical as common intermediate. The same frictional-power dependence of the diastereoselectivity (k inv /k ret ) and the product selectivity ([2]/ [3]) on viscosity (η Ϫα ), in which the α factor represents a measure of the free-volume requirement of the rearrangement process, 7,11 substantiates this conclusion.…”
Section: Introductionmentioning
confidence: 67%